Non-Recurrence Complications of Fibrin Glue Use in Pterygium Surgery: Prevention and Management - Hüseyin Cagatay, Halil (Open Ophthalmol J, 2015)
PURPOSE : To present complications of using fibrin glue in conjunctival-limbal autografting in pterygium surgeries other than recurrences and discuss their prevention and management strategies. MATERIALS AND METHODOLOGY: The charts of all patients who underwent fibrin glue assisted pterygium excision surgery with conjunctival-limbal autograft transplantation from 2010 to 2013 were reviewed. Patients who developed complications except recurrence postoperatively were included in this study. RESULTS : Sixteen (17.39%) of the 92 patients were detected with a complication. Graft dehiscence was diagnosed in 7 (7.6%) patients with 5 of them treated conservatively and 2 patients requiring suturing. Five (5.43%) patients were diagnosed with cyst formation between the graft and conjunctiva or in the graft-removal area; these cysts were primarily excised and no additional problems occurred. Corneal dellen developed in 3 (3.26%) patients and 2 of them regressed after cessation of topical steroids and application of lubricant therapy while one was treated with amniotic membrane transplantation. Residual fibrin glue particles had stiffened on the ocular surface, which resulted in intensive pain and irritation in one (1.08%) patient on the same day of the surgery. The patient’s complaints were reduced by removing these particles from the ocular surface under topical anesthesia. CONCLUSION : Complications in fibrin glue assisted pterygium surgery are relatively different from other techniques. To avoid potential complications of fibrin glue in pterygium surgery, peroperatively ophthalmologists should ensure the conjunctival autograft and conjunctiva are properly adhered, fibrin glue remnants are completely removed from the ocular surface, and no Tenon’s capsule remains between the graft and the conjunctiva.